2022
DOI: 10.1371/journal.pgph.0000194
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with antenatal depression in the Kingdom of Jordan during the COVID-19 pandemic

Abstract: Fear of infection and measures taken to mitigate infection, such as social distancing, lockdown and isolation can lead to anxiety and depression across the life course, but especially in pregnancy. We set out to identify the prevalence of depression in pregnancy, using Edinburgh Postnatal Depression Scale (EPDS) during national quarantine and to examine women’s knowledge, attitude, and practices (KAP) in regard to potential COVID-19-related depression. Following ethical approval, an observational design, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…The current study found that EPDS scores were associated with being a smoker, method of delivery, getting COVID-19, experiencing COVID-19 symptoms, and being admitted to a hospital or ICU. According to a recent study, women who slept longer, had a higher household income, had a higher level of education, lived in a city, were employed, had a gestation of less than six months, and had a husband who was employed with a higher education had statistically significant lower EPDS scores [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current study found that EPDS scores were associated with being a smoker, method of delivery, getting COVID-19, experiencing COVID-19 symptoms, and being admitted to a hospital or ICU. According to a recent study, women who slept longer, had a higher household income, had a higher level of education, lived in a city, were employed, had a gestation of less than six months, and had a husband who was employed with a higher education had statistically significant lower EPDS scores [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…40 Previous studies reported significant levels of depression and anxiety among pregnant women in a number of countries. [22][23][24][25][26] These high levels of depression may be explained by the fact that the formal postnatal health services, usually available to support women and their families were reduced, or in some cases, not available. 11,41 In this study, postnatal low mood was reported significantly more frequently in first-time mothers.…”
Section: Discussionmentioning
confidence: 99%
“…21 A Jordanian study revealed that over one-third of pregnant women (36.7%) reported depressive symptoms during the pandemic, especially those of lower socioeconomic status and those with less understanding of COVID-19 infection. 22 Another study revealed that more than half of pregnant women were feeling anxiety (58.0%) and fear (59.0%). 23 This is comparable with data from other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, nearly 92% of Cov1 and 85% of Cov2 feared infection. Abujilban et al [70] indicated that sufficient knowledge about COVID-19 may be a protective factor against depression during pregnancy. A study by Motrico et al [71] reported that between 33.3% and 47.2% of women during the pandemic experienced perinatal anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%